Strategi Pemasaran dalam Meningkatkan Penjualan pada UMKM Zuana Rasa - Alfiani Ayu Lestari; Citra Savitri; Syifa Pramudita Faddila (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Zuana Rasa's income experiences increases and decreases or fluctuates. This fluctuating income is caused by the lack of implementing appropriate marketing strategies at Zuana Rasa. In order to increase her income, Zuana Rasa must have the right strategy. Zuana Rasa can determine the right marketing strategy by using SWOT analysis so that internal and external factors can be identified which are strengths, weaknesses, opportunities and threats. Therefore, a SWOT analysis is really needed to reduce the obstacles that occur by using the opportunities that exist at Zuana Rasa. The aim of this research is to analyze Zuana Rasa's strengths and weaknesses, so that it can identify opportunities and avoid threats from other competitors. This research uses SWOT analysis with qualitative descriptive research methods. Research data was obtained from primary and secondary data. The results of the research show that the Zuana Rasa Store is in quadrant I supporting an aggressive strategy with an environmental opportunity value of 1.4 and internal strength of 1.8, so the strategy that must be implemented is market growth, market development, product development and market penetration through innovation and development products, promotional development and implementing integrated strategies.